Impact of Sovereign Credit Risk on the Lithuanian Interest Rate on Loans - Kregždė, Arvydas; Murauskas, Gediminas (Ekonomika, 2015)
The paper deals with banks’ interest rates on loans for non-financial corporations and households in Lithuania. It focuses on the influence of the sovereign credit risk on interest rates for loans. The paper presents an analysis of long-run and short-run relationship between interest rates on loans and the financial market indicators EURIBOR and CDS spread. The application of the cointegration technique has revealed that a change in the CDS spread by 100 basis points has an impact on changes in interest rates on loans by 42 basis points in the long run. No evident relationship between CDS spread and interest rates on loans in a short run has been detected. This shows that market conditions do not play a pivotal role for the banks in setting the interest rates on loans in a short run. Some communalities in interest rates on loans in the Baltic states have been established. The main finding is that the sovereign credit risk of Lithuania, expressed as a CDS spread, has a substantial impact on interest rates in the retail credit market of Lithuania in a long run.
Keywords: CDS; spread; credit risk; retail market; loans